1990
DOI: 10.1159/000111846
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylation of Glycolipids in PC12 Cells Is Dependent on the Sequence of Nerve Growth Factor Treatment and Adenylate Cyclase Activation

Abstract: Synthesis of complex glycosphingolipids was analyzed in cultures of PC 12 cells treated with nerve growth factor (NGF) and forskolin, either sequentially or simultaneously. For the sequential treatment, forskolin was added following 15 days of NGF treatment and cultures were continued for 3 additional days. For simultaneous treatment, cells maintained in medium with no additives received both agents and were then incubated for 3 additional days. Sequential NGF/forskolin treatment induced hypertrophy in PC12 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
1
6
1
Order By: Relevance
“…The extent of incorporation returned to the control level 24 h after administration of NGF . This observation is in contrast with Schwarting et al (1990) who reported that the incorporation of [ 1-l4C ]galactose into neutral GSLs of PC12 cells increased only after long-term (3 days) treatment with NGF alone . This discrepancy is most likely attributable to the different cellular responses to NGF by the two different cell lines ; that is, the response to NGF for neurite outgrowth is much quicker for PC12D than for PC 12 cells (Katoh-Semba et al ., 1987) .…”
Section: Discussioncontrasting
confidence: 99%
“…The extent of incorporation returned to the control level 24 h after administration of NGF . This observation is in contrast with Schwarting et al (1990) who reported that the incorporation of [ 1-l4C ]galactose into neutral GSLs of PC12 cells increased only after long-term (3 days) treatment with NGF alone . This discrepancy is most likely attributable to the different cellular responses to NGF by the two different cell lines ; that is, the response to NGF for neurite outgrowth is much quicker for PC12D than for PC 12 cells (Katoh-Semba et al ., 1987) .…”
Section: Discussioncontrasting
confidence: 99%
“…Results reported in this article suggest that the increase in galactose incorporation into glycoproteins observed by Amos et al (1 990) may have been caused by an induction in the levels of GALTase within the Golgi apparatus. In contrast, Schwarting et al ( 1990) reported an increase in fucosylation in PC12 cells treated sequentially with NGF and forskolin, but no change in the incorporation of galactose into these cells. The effect of forskolin treatment alone on galactose incorporation in PC 12 cells was not investigated in this latter study and, therefore, direct comparison with the results observed in F9 cells is not possible.…”
Section: Discussionmentioning
confidence: 82%
“…In these studies, GALTase activity on the cell surface did not change upon cell differentiation induced by NGF. In contrast, recent studies have demonstrated that during PC 12 cell differentiation induced by NGF, galactose incorporation into both neutral glycolipids and gangliosides increased by greater than 100% (Schwarting et al, 1990). Addition of the cyclic AMP (CAMP)-stimulating agent, forskolin, to the NGF-induced cells, however, failed to increase galactose incorporation into these glycolipids.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The mouse mAb AG1 (IgG) recognizes the 140-and 180-kD molecular subtypes of rat NCAM (DiFiglia et al, 1989). The mouse mAbs CC1 and CC6 (IgMs), which recognize unique neuronal glycolipids, have been previously described (Schwarting et al, 1990(Schwarting et al, , 1994. Goat polyclonal antiserum (IgG) against olfactory marker protein (OMP: Hartman and Margolis, 1975) was kindly provided by Dr. F. Margolis.…”
Section: Immunohistochemistrymentioning
confidence: 99%